2015
DOI: 10.3389/fonc.2015.00135
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of pan-PI3K Signaling Synergize with BRAF or MEK Inhibitors to Prevent BRAF-Mutant Melanoma Cell Growth

Abstract: BRAF and MEK inhibitors have improved outcomes for patients with BRAF-mutant melanoma, but their efficacy is limited by both intrinsic and acquired resistances. Activation of the PI3K pathway can mediate resistance to these agents, providing a strong rationale for combination therapy in melanoma. Here, a panel of nine low-passage human metastatic melanoma cell lines with BRAF mutations was tested in cell proliferation and protein expression assays for sensitivity to inhibitors of MEK (selumetinib) and BRAF (ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 50 publications
5
38
0
Order By: Relevance
“…We theorize that isoform 2 may enhance resistance to vemurafenib by activating the PI3K pathway and downregulating the MAPK pathway. This theory is in line with a recent publication which found that pan-PI3K inhibition was able to synergize with BRAF inhibitors to prevent BRAF mutant melanoma cell growth (17). Additionally, studies with the combination of vemurafenib and the MEK inhibitor selumetinib showed that combination with different PI3K pathway inhibitors led to synergistic reduction of cell viability and enhanced apoptosis in vitro (18).…”
Section: Discussionsupporting
confidence: 82%
“…We theorize that isoform 2 may enhance resistance to vemurafenib by activating the PI3K pathway and downregulating the MAPK pathway. This theory is in line with a recent publication which found that pan-PI3K inhibition was able to synergize with BRAF inhibitors to prevent BRAF mutant melanoma cell growth (17). Additionally, studies with the combination of vemurafenib and the MEK inhibitor selumetinib showed that combination with different PI3K pathway inhibitors led to synergistic reduction of cell viability and enhanced apoptosis in vitro (18).…”
Section: Discussionsupporting
confidence: 82%
“…While in vitro studies clearly show the potential of using AKT, pan-PI3K or dual PI3K/mTOR inhibitors in combination with BRAF/MEK inhibitor, the translation into the clinical setting is troublesome due to enhanced systemic toxicities (124)(125)(126)(127)(128). The PI3K family of proteins is relevant in many physiological processes and malignant conditions but nevertheless this interest on the pathway is producing encouraging data advancing in the understanding of melanoma specific PI3K-signaling (129) and lately PI3Kβ isoform specific inhibitors are being developed and trialed in the context of PTEN mutant melanoma patients (130)(131)(132).…”
Section: Potential For Alternative Combination Therapiesmentioning
confidence: 99%
“…(10) Given the current clinical limitations of existing therapies, novel and rationally-designed combination studies with other kinase inhibitors are being explored. (11,12) Despite all efforts to date, the development of resistance to targeted V600E BRAF therapies emerges in virtually 100% of patients treated; acquired drug resistance to this class of agents remains a significant obstacle to dramatically enhanced survival benefits for metastatic melanoma patients.…”
Section: Introductionmentioning
confidence: 99%